Antibiotic Prescribing Practices in Endodontic Infections: A Survey of Dentists in Serbia - Milan Drobac; Katarina Otasevic; Bojana Ramic; Milica Cvjeticanin; Igor Stojanac; Ljubomir Petrovic (MDPI AG, 2021)
The study goal was to provide an overview of antibiotic prescribing practices of Serbian dentists when treating endodontic infections and to disseminate the current ESE (European Society of Endodontology) recommendations to the study participants. A link to an online questionnaire was sent to 628 Serbian dentists whose email addresses were publicly available on the Internet, 158 of whom responded to the survey, resulting in a 25.16% response rate. The significance of possible associations was assessed via the Chi-squared test and Cramer's V measure of association, with p < 0.05 considered as statistically significant. According to the study findings, 55.7% of respondents prescribed a 5-day antibiotic course. Moreover, Amoxicillin 500 mg was the first-choice antibiotic for 55.1% of the respondents, followed by Clindamycin 600 mg (18.4%). For patients allergic to penicillin, 61.4% of respondents prescribed Clindamycin. Statistically significant differences emerged only in relation to acute apical abscess with systemic involvement, whereby dentists aged 46-55 were least likely to prescribe antibiotics in these clinical situations (p = 0.04). Analyses further revealed that recommendations for safe antibiotic prescribing practices were not always followed, as in certain cases, patients were given antibiotics even when this was not indicated. These findings highlight the need for additional education on responsible antibiotic use to prevent bacterial resistance.